'Getting to Know Me': The second phase roll-out of a staff training programme for supporting people with dementia in general hospitals. (January 2018) - Elvish, Ruth; Burrow, Simon; Cawley, Rosanne; Harney, Kathryn; Pilling, Mark; Gregory, Julie; Keady, John
Objectives: The aims were to evaluate a second phase roll-out of a dementia care training programme for general hospital staff and to further develop two outcome scales: the Confidence in Dementia scale for measuring confidence in working with people with dementia and the Knowledge in Dementia scale for measuring knowledge in dementia. Method: Following a 'training the trainers' phase, the study involved the delivery of the 'Getting to Know Me' training programme to a large number of staff (n = 517) across three National Health Service (NHS) Trusts situated in North-West England. The impact of the programme was evaluated using a pre–post design which explored: (i) changes in confidence in dementia, (ii) changes in knowledge in dementia, and (iii) changes in beliefs about behaviours that challenge. Results: Statistically significant change was identified between pre–post training on all outcome measures (Confidence in Dementia: eight point increase, p < 0.001; Knowledge in Dementia: two point increase p < 0.001; controllability beliefs scale: four point decrease, p < 0.001). Medium to large effect sizes were demonstrated on all outcome measures. The psychometric properties of the Confidence in Dementia and Knowledge in Dementia scales are reported. Conclusion: Staff knowledge in dementia and confidence in working with people with dementia significantly increased following attendance at the training sessions. The findings are consistent with preliminary findings and strengthen current knowledge about the impact of dementia care training in general hospitals. The Confidence in Dementia and Knowledge in Dementia scales continue to demonstrate psychometrically sound properties and demonstrate utility in the field of dementia research.